2022
DOI: 10.1128/spectrum.02259-21
|View full text |Cite
|
Sign up to set email alerts
|

Limited Mechanistic Link Between the Monod Equation and Methanogen Growth: a Perspective from Metabolic Modeling

Abstract: The Monod equation has been widely applied to predict the rate of microbial growth, but its application is not always successful. Using a novel metabolic modeling approach, we simulated the growth of a methanogen and uncovered a limited mechanistic link between the Monod equation and the methanogen’s metabolic network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…While these data are consistent with prior observations from studies with Methanothermobacter spp., they diverge from predictions made by metabolic models of Methanosarcina spp. during methanol growth (13). Clearly, more physiological studies like ours are required to bridge the gap between research with enzymes in isolation and systems-level analyses of methanogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these data are consistent with prior observations from studies with Methanothermobacter spp., they diverge from predictions made by metabolic models of Methanosarcina spp. during methanol growth (13). Clearly, more physiological studies like ours are required to bridge the gap between research with enzymes in isolation and systems-level analyses of methanogens.…”
Section: Discussionmentioning
confidence: 99%
“…No direct evidence linking MCR abundance to growth and methanogenesis is currently available, and there are differing views literature. A recent study used a kinetic and stoichiometric hybrid approach to model the growth of Methanosarcina barkeri on methanol (13). Here, they showed MCR has a high control coefficient (of ∼0.9) during growth on high methanol concentrations (> 15 mM) i.e., that small changes in MCR levels have a dramatic impact on growth rate under typical batch-culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In 1942, Monod, the founder of cellular growth kinetics, proposed a hyperbolic relationship between the concentration of substrate and cell growth kinetics (i.e., the Monod model, see Equation (1)) [ 18 ]. The Monod kinetic model describes the growth kinetics of cells through thousands of enzymes, which is the most widely used unstructured kinetic model [ 19 ]. For example, Pau et al described the uptake rates of the substrates, glucose and xylose, and the inhibitors using a Monod-type kinetic model in the lignocellulosic fermentation [ 20 ].…”
Section: Development Of Modelingmentioning
confidence: 99%
“…No direct evidence linking MCR abundance to growth and methanogenesis is currently available, and there are differing views in literature. A recent study used a kinetic and stoichiometric hybrid approach to model the growth of Methanosarcina barkeri on methanol ( 13 ). They showed that MCR has a high control coefficient (of ~0.9) during growth on high methanol concentrations (> 15 mM), i.e., small changes in MCR levels will have a dramatic impact on growth rate under typical batch-culture conditions.…”
Section: Introductionmentioning
confidence: 99%